The cutaneous bacterium Janthinobacterium lividum inhibits the growth of Trichophyton rubrum in vitro. (22nd August 2013) - Ramsey, Jeremy P.; Mercurio, Albert; Holland, Jessica A.; Harris, Reid N.; Minbiole, Kevin P. C.
Abstract Background Tinea pedis (athlete's foot) is a fungal infection that is both widespread and challenging to treat. Standard treatments consist of topical and systemic therapies of antifungal agents, such as miconazole, itraconazole, and terbinafine. The extended nature of topical therapy and the toxicity of long‐term systemic therapy limit the utility of current treatments. An alternate approach relies on an understanding of bacterial–fungal interactions. Specifically, a probiotic antifungal bacterium such as Janthinobacterium lividum can counter infection; Janthinobacterium is a major constituent of the human skin microbiota. Janthinobacterium lividum has been shown to ameliorate the effects of the cutaneous fungal disease chytridiomycosis in a vertebrate species (Rana muscosa). Methods Dual‐culture plate challenge assays were performed using J. lividum and Trichophyton rubrum, the leading cause of athlete's foot. Results In all cases, T. rubrum colonies grew significantly smaller when co‐cultured with J. lividum. Conclusion These in vitro results suggest that J. lividum merits further investigation as a human cutaneous probiotic.